Myocilin Interacts with Syntrophins and Is Member of Dystrophin-associated Protein Complex - Joe, Myung Kuk (American Society for Biochemistry and Molecular Biology, 2012)
Genetic studies have linked myocilin to open angle glaucoma, but the functions of the protein in the eye and other tissues have remained elusive. The purpose of this investigation was to elucidate myocilin function(s). We identified α1-syntrophin, a component of the dystrophin-associated protein complex (DAPC), as a myocilin-binding candidate. Myocilin interacted with α1-syntrophin via its N-terminal domain and co-immunoprecipitated with α1-syntrophin from C2C12 myotubes and mouse skeletal muscle. Expression of 15-fold higher levels of myocilin in the muscles of transgenic mice led to the elevated association of α1-syntrophin, neuronal nitric-oxide synthase, and α-dystroglycan with DAPC, which increased the binding of laminin to α-dystroglycan and Akt signaling. Phosphorylation of Akt and Forkhead box O-class 3, key regulators of muscle size, was increased more than 3-fold, whereas the expression of muscle-specific RING finger protein-1 and atrogin-1, muscle atrophy markers, was decreased by 79 and 88%, respectively, in the muscles of transgenic mice. Consequently, the average size of muscle fibers of the transgenic mice was increased by 36% relative to controls. We suggest that intracellular myocilin plays a role as a regulator of muscle hypertrophy pathways, acting through the components of DAPC.